(untitled) (Bangladesh Journal of Agricultural Research, 2014)
Grain cereals are the food security staples of the poor masses around the globe. However, a significant proportion of these crops, especially cowpea are lost during storage. This is more so the case in Africa where postharvest losses due to the absence of efficient storage for cowpea is alarming: between 30-70 percent. This study, therefore, examined the adoption of improved cowpea storage practices/facilities by cowpea farmers and traders in Nigeria, using Kwara State as case study. The study specifically investigated factors affecting cowpea storage practices. For the study, 180 households involved in cowpea storage activities were selected across the study area and interviewed. Data analysis tools were the descriptive statistics and logistic regression tools. The descriptive statistics was employed to analyse the socio-economics and cowpea storage practices of respondents, while the logistic regression tool was used to identify factors affecting respondents likelihood to adopt popular improved cowpea storage technique crib in the study area. The study results indicate that most of the respondents have not had any form of formal education. The common storage agro-chemicals used by the respondents were actellic liquid, actellic dust, and phostoxin. Crop storage practices identified in the study area were the traditional ones, involving the use of old drums, jute bags, earthen pots, gourds and rhumbus. The improved/modern storage practices identified comprised the use of cribs and a handful patronage of public silos. Logistic regression results showed that the perception of respondents about storage pest as threats to their crops, their household size, and credit availability variables are significant at 5 percent level, implying that these variables determine respondents likelihood to adopt the crib storage technique for their cowpea. However, the type of education whether formal or informal acquired by the respondents variable is insignificant and therefore, does not determine respondents likelihood to adopt the crib storage technique for their crops. Factor identified as constraints to efficient storage practices were inadequate credit facilities, high costs of and poor access to improved storage facilities. The study, therefore, concludes that there is an urgent need for the provision of credit facilities to cowpea farmers and grain traders alike, subsidy on improved storage facilities and ease of access to the improved storage facilities DOI: http://dx.doi.org/10.3329/bjar.v39i1.20079 Bangladesh J. Agril. Res. 39(1): 47-57, March 2014